2014
DOI: 10.1007/s10620-014-3346-5
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Recognition and Evaluation of Incidentally Identified Hepatic Steatosis

Abstract: Background Nonalcoholic fatty liver disease (NAFLD), the most common cause of liver disease, is frequently diagnosed incidentally on imaging. The goal of the present study was to characterize rates of documentation and evaluation of incidentally identified steatosis. Methods Adults who underwent abdominal computed tomography (CT) with incidentally reported steatosis from January 2008 to October 2011 were identified. Individuals with ≥1 primary care appointments within 14 months following imaging were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Documenting hepatic steatosis in both the body and conclusion sections compared to just the body of the radiology report resulted in more frequent documentation in medical charts and discharge summaries. This was also shown in a study of 127 patients with incidental hepatic steatosis and infrequent documentation in medical charts . Unfortunately, this is expected as clinicians may not necessarily read the body of report and may rely on the conclusion section to answer specific clinical questions in a busy emergency work environment.…”
Section: Discussionmentioning
confidence: 91%
“…Documenting hepatic steatosis in both the body and conclusion sections compared to just the body of the radiology report resulted in more frequent documentation in medical charts and discharge summaries. This was also shown in a study of 127 patients with incidental hepatic steatosis and infrequent documentation in medical charts . Unfortunately, this is expected as clinicians may not necessarily read the body of report and may rely on the conclusion section to answer specific clinical questions in a busy emergency work environment.…”
Section: Discussionmentioning
confidence: 91%
“…It has been recognized that using ultrasound to detect hepatic steatosis is not cost-effective because clinically relevant fibrosis is present in no more than 11% of cases. (23,24) The utility of other modalities, including elastography, which is potentially more effective but costlier, has not yet been proven. Although liver biopsy is required to diagnose NASH, only patients at high risk require this evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the majority of patients had not previously been diagnosed with NAFLD by imaging or liver biopsy prior to being diagnosed with cirrhosis. Under‐recognition of NAFLD appears to be common, with two studies finding the majority of patients in primary care who had incidental findings of elevated alanine aminotransferase levels or hepatic steatosis on imaging were not subsequently evaluated for NAFLD . Similarly, a recent study of patients with NAFLD cirrhosis who were listed for liver transplant showed that the majority of these patients were not aware of an underlying NAFLD diagnosis until they presented with complications of portal hypertension .…”
Section: Discussionmentioning
confidence: 99%
“…The decision to screen patients with NAFLD for cirrhosis may be hampered by an underestimation of disease prevalence or a lack of regard for NAFLD as a clinically important condition . Correspondingly, patients with NAFLD cirrhosis are at risk of remaining undiagnosed, with only 0%‐3% of patients with NAFLD in primary care with a high NFS either recognized or referred for specialist review . Anecdotal clinical experience also suggests that a significant proportion of patients with NAFLD are unintentionally (or incidentally) discovered to be cirrhotic during the investigation of alternative medical conditions unrelated to their liver disease.…”
Section: Introductionmentioning
confidence: 99%